THE IMPACT OF SERVICE QUALITY ON BRAND LOYALTY OF DTAC SELULER SERVICE USERS - Debby Arisandi (Universitas Bunda Mulia, 2017)
Purpose- In the GSM seluler telephony sector, the main condition for protecting the subscriber base is to win customer to be loyalty, a key necessity for the maintenance of a brand loyalty in the long term. To achieve this aim, service quality must be measured and identified. This paper’s aim is to measure the effects of service quality towards brand loyalty on DTAC seluler service provider. This study will explore the relationship between service quality and brand loyalty in the seluler service industry.Design/methodology/approach- The main research target sample covered 200 seluler phone users in Prince of Songka University, Hatyai campus. Field research was conducted. The questionnaire was formed by a synthesis of existing constructs in relevant literature. Reliability tests, descriptive statistic, and regressions analyses were performed to both confirm scale reliability and answer the research questions. The data were analysed by moderated regression analysis to test the hypotheses.Findings- The findings of this study show that an overall service quality directly affects brand loyalty. Network quality, customer service, pricing structure and billing system are the service quality dimensions that have significant positive influence on brand loyalty, which in turn has a significant positive impact on brand loyalty 43,5%. Therefore, it plays a crucial role in winning customer loyalty.Originality/value- It is of great importance for seluler operators in a mature market such as that of Thailand, to understand what the drivers of brand loyalty are. The present study produced useful findings, which can be utilized by seluler service provider managers, in their effort to develop and implement successful brand loyalty strategies. With respect to the findings, pricing structure has the most importance than others dimensions of service quality which provides positive outcomes on brand loyalty, not only in the present but also in the future. So, the effect of pricing structure on brand loyalty becomes greater than the effect of others dimenstions of service quality. Therefore, any GSM operator who wishes to preserve its existing subscriber base should concentrate on winning its subscribers’ loyalty, especially for DTAC.Keywords- Seluler Services, Brand Loyalty, Service Quality